The magisterium-theology relationship: contemporary theological conceptions in the light of Universal Church teaching since 1835 and the pronouncements of the Bishops of the United States - Figueiredo, Anthony J. (Tesi gregoriana / Serie teologia, 2001)
The author offers an historical and systematic analysis of magisterial documents from 1835 to the present day, addressing such important issues as the relationship between theological reasoning and magisterial statement, dissent, the natural moral law, the grades of Church teaching and the conditioning of dogma. He identifies areas of difficulty, points out contradictions, offers solutions, calls for further reflection and determines the definitive foundation for a correct rapport between magisterium and theologians.